2011
DOI: 10.1371/journal.pgen.1001369
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Cell Type–Specific Expression Patterns in the Human Mammary Epithelium

Abstract: Differentiation is an epigenetic program that involves the gradual loss of pluripotency and acquisition of cell type–specific features. Understanding these processes requires genome-wide analysis of epigenetic and gene expression profiles, which have been challenging in primary tissue samples due to limited numbers of cells available. Here we describe the application of high-throughput sequencing technology for profiling histone and DNA methylation, as well as gene expression patterns of normal human mammary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
83
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 38 publications
9
83
0
1
Order By: Relevance
“…Similar data were described for breast cell differentiation. 33 These findings are consistent with a recent hypothesis that histone modifications indicate, instead of tight regulation of transcription, fine-tuning of transcription to ensure a certain chromatin state that allows the proper execution of transcriptional control. 40 Overall, our results suggest that genome-wide histone modifications are important to determine stem or progenitor cell states in AML.…”
Section: Patients and Cells Peripheral Blood Samples In Aml Patientssupporting
confidence: 91%
See 1 more Smart Citation
“…Similar data were described for breast cell differentiation. 33 These findings are consistent with a recent hypothesis that histone modifications indicate, instead of tight regulation of transcription, fine-tuning of transcription to ensure a certain chromatin state that allows the proper execution of transcriptional control. 40 Overall, our results suggest that genome-wide histone modifications are important to determine stem or progenitor cell states in AML.…”
Section: Patients and Cells Peripheral Blood Samples In Aml Patientssupporting
confidence: 91%
“…23,33 Our data suggest that histone modifications also mediate stem cell to differentiated cell transition in cancer. In general we found as expected that K4 marks are concentrated at TSS whereas K27 marks are distributed broadly.…”
Section: Patients and Cells Peripheral Blood Samples In Aml Patientsmentioning
confidence: 75%
“…Trimethylated Histone H3 lysine 4 (H3K4me3) was analyzed using chromatin immunoprecipitation (ChIP) as described previously (13,14). Details of the experimental procedures are provided in the Supplementary Methods.…”
Section: Quantitative Rt-pcr Of Hotairmentioning
confidence: 99%
“…25 However, they focused mainly on tumor epithelial cells and there was little in-depth study on the potential involvement in tumor progression of other epithelial and myoepithelial cells or of the stroma. 26 Other studies have reported somatic genetic alterations, including gene copy number changes, microsatellite instability (MSI) and point mutations in tumor suppressor genes, and oncogenes in breast tumor stroma. [27][28][29][30][31][32][33][34] In 2004, Fukino 31 compared global genomic alterations between carcinomatous epithelium and tumor stroma from 134 sporadic invasive breast carcinoma samples.…”
Section: Role Of Microenvironment In Tumor Initiation and Progressionmentioning
confidence: 99%